2012
DOI: 10.1016/j.juro.2012.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life in Adolescents with Bladder Exstrophy-Epispadias as Measured by the Child Health Questionnaire-Child Form 87

Abstract: Purpose We determined health related quality of life as reported by adolescents with bladder exstrophy or epispadias using a validated generic instrument. Materials and Methods Adolescents age 11 to 18 years with bladder exstrophy or epispadias (57) completed a validated, generic, health related quality of life instrument, the CHQ-CF87 (Child Health Questionnaire-Child Form 87). Urinary incontinence, catheterization status, and medical and surgical history data were also obtained. Mean summary scores and 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…HRQoL was not reduced in the study from Boston in 8-to 25-year-old BE patients when measured with Pediatric Quality of Life Inventory or in another study from the United States of America, in which 49 adolescent BEE patients were evaluated with Child Health Questionnaire-Child Form 87. 12,13 In our study, BE patients had a tendency to poorer scores in all dimensions of HRQoL and psychiatric symptoms than epispadias patients. However, significant difference was observed only in somatization scores.…”
Section: Commentmentioning
confidence: 45%
See 1 more Smart Citation
“…HRQoL was not reduced in the study from Boston in 8-to 25-year-old BE patients when measured with Pediatric Quality of Life Inventory or in another study from the United States of America, in which 49 adolescent BEE patients were evaluated with Child Health Questionnaire-Child Form 87. 12,13 In our study, BE patients had a tendency to poorer scores in all dimensions of HRQoL and psychiatric symptoms than epispadias patients. However, significant difference was observed only in somatization scores.…”
Section: Commentmentioning
confidence: 45%
“…Similarly, the incontinent BEE patients have been shown to have a tendency to poorer HRQoL in most dimensions of Child Health Questionnaire-Child Form 87. 13 In our material, the patients with the need of diapers had a tendency to poorer scores of HRQoL and more psychiatric symptoms than the patients with more occasional or mild incontinence or bladder augmentation. Of interest, none of the incontinent patients were interested in bladder augmentation in a phone or outpatient clinic discussion at the end of the study, in spite of our national social security system, when informed that CIC program is needed after the operation.…”
Section: Commentmentioning
confidence: 56%
“…Cette appréciation de la qualité de la vie ne va sans problèmes méthodologiques, mais elle doit faire partie des éva-luations dans les ADS, aussi bien chez l'enfant [27] que chez l'adulte [28,29].…”
Section: La Qualité De La Vieunclassified
“…For example, as discussed in this issue of The Journal, Schaeffer et al (page 1924) found that despite expectations to the contrary, adolescents with the bladder epispadias-exstrophy complex demonstrated surprisingly robust self-esteem. 7 Other evidence indicates that measuring HRQOL can bolster medical decision making. However, as Varni et al noted, the ability of HRQOL measures to meaningfully support medical decision making depends on the measures being easily administered and interpretable.…”
mentioning
confidence: 99%